Harnessing the Storm: Leveraging Conflict Management as a Driver for Organizational Innovation - Uryatul Hikmah; Ittaqillah Haisuma Kunta; Hefniy Hefniy (Universitas Nurul Jadid Probolinggo, Indonesia, 2025)
Study This aiming at For analyze How management conflict can utilized as driver innovation organization, as well as identify strategy effective in manage conflict to produce mark add. Method research used is approach qualitative with studies literature and analysis cases in some successful organization manage conflict in a way constructive. Data collected through study journal scientific, report organizations and resources relevant others, then analyzed in a way thematic. Research results show that managed conflict in a way open, collaborative, and based communication effective capable increase creativity, enrichment perspective, as well as push birth solution innovative. On the other hand, the conflict is ignored or managed in a way repressive precisely hinder performance and innovation. Factors key success covering leadership transformational, culture inclusive organizations, as well as system transparent communication. Implications study This confirm that organization need change paradigm to conflict, from something that must be done avoided become opportunity strategic For innovation. Therefore that, development competence management conflict for leaders and members organization become very important use create environment adaptive and innovative work.